The Effects of the COVID-19 Pandemic on Teaching/Learning and Wellbeing/Social Interactions in a sample of Irish Primary Schools - Corkery, Brian (Trinity College (Dublin, Ireland). School of Education, 2022)
This research examines the impact COVID-19 has had on teaching/learning in Irish primary schools. The effect on the welfare of primary school pupils is also investigated as is the disruption caused to their social interactions. The research briefly looks at the period March - June 2020 and the return to school in August/September 2020. An in-depth study is conducted on the period January - March 2021 (second school closure) and the period from March 2021 when the schools reopened. Chapter one provides an introduction, the background, the aims, and objectives along with the structure of this research project. In chapter two, the review of available literature is undertaken on the effects of enforced school closures. In particular, the consequences the current COVID-19 pandemic had on teaching/learning and wellbeing/social interactions are explored. Chapter three outlines the research methods used along with an explanation of how the data was correlated. An unexpected variety of enlightening findings are presented in chapter four. Chapter five contains a detailed analysis of the findings extracted from both the qualitative and quantitative research methods used. The impact of teaching/learning and wellbeing/social interactions was examined from the perspectives of primary school teachers and that of primary school pupils. This research has resulted in a number of recommendations being proposed, along with highlighting a variety of limitations encountered during the process. Topics for further research are offered.
Keywords: Leadership and Management; Education